Group process for diagnosis disclosure to children living with HIV/AIDS: an experience report (Research, Society and Development, 2023)
The current reality of Acquired Immunodeficiency Syndrome (AIDS) as a chronic disease brought some challenges for caregivers and health professionals. Among these, diagnosis disclosure, that is, telling the individual that he or she has been infected with the human immunodeficiency virus (HIV), stands out as an extremely complex issue and especially delicate with the subject is a child. Despite the family's reluctance to tell the child that he or she has HIV, the diagnosis disclosure brings benefits to the patient, caregivers and health professionals. This study is an experience report of the process of disclosure of HIV/AIDS diagnosis to seropositive children monitored by the multidisciplinary team of pediatric infectology, in a tertiary hospital in the interior of the state of São Paulo. It is a follow-up in groups of patients and their caregivers, coordinated by the occupational therapist and the psychologist. The process of diagnosis disclosure was organized in stages: initial assessment; group activities for explanations about HIV/AIDS and its action on the body; diagnosis disclosure; further follow-up and reassessment. It is believed that the diagnosis disclosure is a milestone for the construction of a new history and identity. When children obtain realistic information about their health condition, they can understand the importance of medications, which contributes to adherence to treatment. The disclosure of the diagnosis also favors the adaptation of patients to seropositivity, allowing them to develop coping skills to deal with this condition.